(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
Because they improve student engagement, encourage interactive learning, and enhance instructional activities, digital educational technologies are essential to the modernization of higher education institutions. This study highlights the usefulness of digital educational technologies in creating dynamic learning environments by classifying them according to how they are used in instructional procedures. Learning management systems (LMS), virtual and augmented reality (VR/AR), tools driven by artificial intelligence (AI), gamification techniques, cloud-based learning platforms, and Internet of Things (IoT) applications are all included in this category. The study also looks at how these technologies affect individualized learning, student performance, and the direction of digital education.